PENGARUH KUALITAS AUDIT, AUDIT REPORT LAG TERHADAP OPINI AUDIT GOING CONCERN - Sagala, Joyce Margaretha; Hutabarat, Francis (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2022)
The purpose of this study is to find out whether audit quality and audit lag can affect going concern audit opinions during the 2018-2020 period in property and real estate sub-sector companies. This study uses secondary data obtained from company auditor reports taken on the Indonesia Stock Exchange website or www.idx.co.id. In this study, there were 159 companies studied during the 2018-2020 period. The test results in the hypothesis used are logistic regression analysis which results that audit quality does not affect going concern audit opinion while audit lag affects going concern audit opinion.